A Study on Consumer Preference towards Selected Bike in Hanamkonda Town - N.Revathi, Muniganti Praveen (International Journal of Scientific Research and Management (IJSRM), 2016)
In Warangal district, hanamkonda town was selected to find the consumer preference towards selected bike. The most important job of marketers is to "think of consumers" and to guide companies and nonprofit organizations into developing offers that are meaningful and attractive to target consumers. To find the consumer factors which influence them to buy the particular brand of bike and their level of satisfaction about the usage of bike. Global demand for motorcycles is expected to advance to 6% annually to 59 million units by 2011 to now. The Indian two wheeler industry began a modest start in the 1950's and witnessed spectacular growth over the last 5 years. Bikes constitute 80% of the two wheelers sold every year.